PENGARUH KOMPOSISI MEDIA TANAM KOMPOS JERAMI DAN KAPAS TERHADAP KOMPONEN HASIL DAN HASIL JAMUR MERANG (Volvariella volvacea) - Sanaji Sanaji; Wijaya Wijaya; I Ketut Sukanata (Agroswagati Jurnal Agronomi, 2017)
The objectives of this study were: (1) To determine the effect of the combination treatment of the composition of the planting media of straw and cotton compost on the yield and yield components of the mushroom (Volvariella volvaceae), and (2) Knowing the combination treatment of the composition of the straw and cotton compost best for the yield components and results of the mushroom (Volvariella volvaceae).The experiments have been carried out at the Agricultural, Fisheries, Plantation and Forestry Counseling Center (BP3K) in Panguragan District, Kalianyar Village. The trial location is at an altitude of 8 m above sea level. The average daily temperature is 30 0C and the average humidity is 85%. The location selection was based because the Karanganyar village had developed mushroom cultivation. The research period has been carried out for four months starting from September to December 2012.The results showed that: (1) The combination of the treatment composition of the planting medium of straw compost and cotton compost had a significant effect on the number of fruit bodies per plot and fruit body weight per batch, but did not significantly affect fruit body length, fruit body diameter and weight per fruiting bodies, and (2) In combination with the treatment of planting media straw compost and cotton compost with a ratio of 1: 1, 2: 1, 3: 1, 4: 1 and 5: 1 obtained the number of fruit bodies per plot and fruit body weight per plot tall one.